Respuesta :

Answer:

C

Step-by-step explanation:

y = 3x + 1

2y = 6x + 2 but when we divide both sides by 2 we see

y = 3x + 1 which is exactly the same as the first equation.

therefore we have ultimately only one equation for an equation with 2 variables, which has infinitely many solutions.

Esther

Answer:

This equation has infinitely many solutions.

Step-by-step explanation:

y = 3x + 1

2y = 6x + 2

-2(y = 3x + 1) ==> -2y = -6x = -2

1 (2y = 6x + 2) ==> 2y = 6x + 2

-2y = -6x = -24

   2y = 6x + 2

      0 =0

Hope this helps!

ACCESS MORE